Acute mental health presentations before and during the COVID-19 pandemic. Issue 4 (16th July 2021) - Mukadam, Naaheed; Sommerlad, Andrew; Wright, Jessica; Smith, Abigail; Szczap, Aleksandra; Solomou, Solomis; Bhome, Rohan; Thayalan, Roshan; Abrol, Esha; Aref-Adib, Golnar; Maconick, Lucy; Aubrey-Jones, Dominic; et al.
Abstract : Background: A number of community based surveys have identified an increase in psychological symptoms and distress but there has been no examination of symptoms at the more severe end of the mental health spectrum. Aims: We aimed to analyse numbers and types of psychiatric presentations to inform planning for future demand on mental health services in light of the COVID-19 pandemic. Method: We analysed electronic data between January and April 2020 for 2534 patients referred to acute psychiatric services, and tested for differences in patient demographics, symptom severity and use of the Mental Health Act 1983 (MHA), before and after lockdown. We used interrupted time-series analyses to compare trends in emergency department and psychiatric presentations until December 2020. Results: There were 22% fewer psychiatric presentations the first week and 48% fewer emergency department presentations in the first month after lockdown initiated. A higher proportion of patients were detained under the MHA (22.2 v . 16.1%) and Mental Capacity Act 2005 (2.2 v . 1.1%) ( χ 2 (2) = 16.3, P < 0.0001), and they experienced a longer duration of symptoms before seeking help from mental health services ( χ 2 (3) = 18.6, P < 0.0001). A higher proportion of patients presented with psychotic symptoms (23.3 v . 17.0%) or delirium (7.0 v . 3.6%), and fewer had self-harm behaviour (43.8 v . 52.0%, χ 2 (7) = 28.7, P < 0.0001). A higher proportion were admitted to psychiatric in-patient units (22.2 v . 18.3%) ( χ 2 (6) = 42.8, P < 0.0001) after lockdown. Conclusions: UK lockdown resulted in fewer psychiatric presentations, but those who presented were more likely to have severe symptoms, be detained under the MHA and be admitted to hospital. Psychiatric services should ensure provision of care for these patients as well as planning for those affected by future COVID-19 waves.